Nudging construction workers towards better sun-safety behaviour: summary of the evidence for practitioners. Issue 1 (2nd January 2020) - Nioi, Amanda; Wendelboe-Nelson, Charlotte; Cowan, Sue; Cherrie, Mark; Rashid, Shahzad; Cowie, Hilary; Davis, Alice; Ritchie, Peter; Lansdown, Terry C.; Cherrie, John W.
Abstract: Excessive exposure to solar ultra-violet (UV) radiation can cause skin cancer, but inadequate exposure to sunlight limits the production of vitamin D. We report a text messaging and supportive smartphone app intervention to reduce UV exposure in the summer and promote vitamin D intake in winter. Results suggest that many workers had insufficient circulating vitamin D in winter, but for the intervention group vitamin D levels increased significantly compared to the control group. In summer, workers were exposed to relatively high UV levels, which were sufficient to importantly increase their risk skin cancer. The sun-safe intervention failed to reduce exposure to solar UV, which we attribute to an entrenched belief that a suntan is desirable. We argue that a more prescriptive risk-based approach is needed to reduce the risk of skin cancer among outdoor construction workers. Graphical Abstract: